Welcome to Westonci.ca, your one-stop destination for finding answers to all your questions. Join our expert community now! Join our platform to connect with experts ready to provide precise answers to your questions in different areas. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.

Determine the input [tex]\( x \)[/tex] that would give an output value of [tex]\(\frac{2}{3}\)[/tex] for the function [tex]\( f(x) = -\frac{1}{3}x + 7 \)[/tex].

[tex]\[
\begin{array}{l}
\frac{2}{3} = -\frac{1}{3} x + 7 \\
-\frac{19}{3} = -\frac{1}{3} x \\
x =
\end{array}
\][/tex]


Sagot :

Let's solve for the input [tex]\( x \)[/tex] that gives an output value of [tex]\( \frac{2}{3} \)[/tex] in the function [tex]\( f(x) = -\frac{1}{3}x + 7 \)[/tex].

1. Start with the given function and set it equal to [tex]\( \frac{2}{3} \)[/tex]:
[tex]\[ \frac{2}{3} = -\frac{1}{3}x + 7 \][/tex]

2. To isolate the term with [tex]\( x \)[/tex], subtract 7 from both sides of the equation:
[tex]\[ \frac{2}{3} - 7 = -\frac{1}{3}x \][/tex]

3. Simplify the left side:
[tex]\[ \frac{2}{3} - 7 = \frac{2}{3} - \frac{21}{3} = \frac{2 - 21}{3} = -\frac{19}{3} \][/tex]

4. Now, we have:
[tex]\[ -\frac{19}{3} = -\frac{1}{3}x \][/tex]

5. To solve for [tex]\( x \)[/tex], multiply both sides of the equation by [tex]\(-3\)[/tex]:
[tex]\[ x = \left(-\frac{19}{3}\right) \times (-3) \][/tex]

6. Simplifying this, we get:
[tex]\[ x = 19 \][/tex]

Therefore, the input [tex]\( x \)[/tex] that results in an output value of [tex]\( \frac{2}{3} \)[/tex] is [tex]\( x = 19 \)[/tex].